The Influence of Regional Asset Management, HR Competence, and Utilization of Information Technology on the Quality of Financial Reports (Case Study at the Surakarta City Tourism Office) - Heri Kusmariyanto; Kartika Hendra Titisari; Agni Astungkara (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The financial statements presented must have the quality of information as contained in the principles and applicable laws. To maintain the quality of financial reports, it is necessary to manage regional assets, human resource competencies, and use information technology. This study aims to determine the effect of regional asset management, human resource competence, and the use of information technology on the quality of financial reports. This research is quantitative. The population consists of 35 employees of the Surakarta City Tourism Office. The number of samples is 35 people with saturated sampling technique. The data analysis technique used multiple linear regression analysis. This research is indicated by the results of Result of t count > t table (3.327 > 2.040), sig. of 0.002 < 0.05, meaning that the management of regional assets affects the quality of financial reports at the Surakarta City Tourism Office. Hypothesis 1 is proven true. The result of t count > t table (2,453 > 2,040), sig. of 0.020 < 0.05, it means that H2 is accepted, meaning that human resource competence affects the quality of financial reports at the Surakarta City Tourism Office. Hypothesis 2 is proven true. The result of t count > t table (2,159 > 2,040), sig. of 0.039 < 0.05, meaning that the use of information technology affects the quality of financial reports at the Surakarta City Tourism Office. Hypothesis 3 is proven true.